A perspective on the role of class III semaphorin signaling in central nervous system trauma - Mecollari, Vasil; Nieuwenhuis, Bart; Verhaagen, Joost (Frontiers in Cellular Neuroscience, 2014)
Traumatic injury of the central nervous system (CNS) has severe impact on the patients’ quality of life and initiates many molecular and cellular changes at the site of insult. Traumatic CNS injury results in direct damage of the axons of CNS neurons, loss of myelin sheaths, destruction of the surrounding vascular architecture and initiation of an immune response. Class III semaphorins (SEMA3s) are present in the neural scar and influence a wide range of molecules and cell types in and surrounding the injured tissue. SEMA3s and their receptors, neuropilins (NRPs) and plexins (PLXNs) were initially studied because of their involvement in repulsive axon guidance. To date, SEMA3 signaling is recognized to be of crucial importance for re-vascularization, the immune response and remyelination. The purpose of this review is to summarize and discuss how SEMA3s modulate these processes that are all crucial components of the tissue response to injury. Most of the functions for SEMA3s are achieved through their binding partners NRPs, which are also co-receptors for a variety of other molecules implicated in the above processes. The most notable ligands are members of the vascular endothelial growth factor (VEGF) family and the transforming growth factor family. Therefore, a second aim is to highlight the overlapping or competing signaling pathways that are mediated through NRPs in the same processes. In conclusion, we show that the role of SEMA3s goes beyond inhibiting axonal regeneration, since they are also critical modulators of re-vascularization, the immune response and re-myelination.